THE EFFECT OF PRICE ON CUSTOMER LOYALTY WITH CONSUMER SATISFACTION AS A MODERATING VARIABLE (STUDY ON INDOMIE CONSUMERS IN SRAGEN DISTRICT) - Kissi Mandriyani; Triyanto (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
The purpose of this study is to ascertain how price affects customer loyalty, how consumer satisfaction affects customer loyalty, and how price affects customer loyalty in the Sragen District, as mediated by consumer satisfaction. Customers who purchase Indomie in the Sragen District serve as the population's research sample. Using an accidental sampling strategy, which involves selecting people of the population who are discovered incidentally (by chance), the sample for this study included 100 respondents. The method of gathering data makes use of a questionnaire. The following analytical tools are employed: hypothesis testing (path analysis), t-test, F test, coefficient of determination test (R2), classical assumptions (normality, multicollinearity, and heteroscedasticity tests), and instrument testing (validity, reliability, and validity tests). According to the study, price significantly affects Indomie customers' loyalty in the Sragen District. Price is having a substantial impact on Indomie consumer satisfaction in the Sragen District. Sragen Districi's Indomie client loyalty is significantly impacted by customer satisfaction. Indomie consumer satisfaction in the Sragen District acts as a mediator between price and customer loyalty.